Prognostic impact of tumor size on isolated hepatocellular carcinoma without vascular invasion may have age variance - Zhang, Yi; Zhang, Jun-Gang; Yu, Wei; Liang, Lei; Wu, Chun; Zhang, Cheng-Wu; Xie, Ya-Ming; Huang, Dong-Sheng; Shi, Ying (Frontiers in Surgery, 2023)
Background: Previous studies suggested that tumor size was an independent risk factor of prognosis for hepatocellular carcinoma (HCC). However, the general prognostic analysis did not consider the interaction between variables. The purpose of this investigation is to explore whether the effect of tumor size on cancer-specific survival (CSS) varies with other variables. Methods: All patients diagnosed with HCC from 2010 to 2015 were extracted from the Surveillance, Epidemiology, and End Results (SEER) database, whose tumors were isolated and without macrovascular invasion. We conducted interaction test between tumor size and other variables to determine whether the whole cohort need to be stratified according to the variable. In addition, we performed trend test for tumor size and calculated the values of per 1 SD. Results: After screening, we got 1,920 patients who met our requirements. Multivariable analysis of the whole cohort showed that age, gender, tumor size, pathological grade and marital status were independent risk factors for CSS. Interaction test revealed that there existed interaction between age and tumor size (p for interaction<0.05). Stratified analysis of patients by age showed that tumor size was an independent risk factor (HR:1.010; 95%CI 1.007 , 1.013; p < 0.001) when patient's age≤65 years old. On the contrast, tumor size was not an independent risk factor when patient's age > 65 years old. This result was confirmed by trend analysis (p for trend < 0.001), and the patient's CSS risk increased by 42.1% for every one standard deviation increase in tumor size. Conclusion: Tumor size was not an independent risk factor when patient's age >65 years. Therefore, when analyzing the relationship between tumor size and CSS of isolated HCC without vascular invasion, stratified analysis should be performed according to age.